A new genus and a new species of Cladonotinae (Orthoptera: Tetrigidae) from Mindanao, Philippines - Tan, Ming Kai; Tumbrinck, Josef; Rivera, Rodrin R.; Nuñeza, Olga Macas (Zootaxa, 2024)
A new genus and a new species of Cladonotinae (Orthoptera: Tetrigidae) is described from Mount Malindang in Mindanao, Philippines: Fartmanntettix undulatus Tan & Tumbrinck, gen. et sp. nov. Tentatively, we classify this new genus under the tribe Trusmaditetrigini Storozhenko, 2023 consisting of eight genera (including the new genus described here). This new genus is characterised from other representatives of the tribe by the distinctly undulated and raised carinae on the pronotum and femora. A key to the genera of the tribe is also provided.